What Matters to Malaysian Students Retention: University Image or External Environment? (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Malaysia, the growth of higher education institutions provides not only more opportunities but increasing competition within the industry. Despite its enormous potential, investigating student retention and its antecedents will provide vital input for the industry to sustain and strategize the most appropriate marketing actions. Therefore, this study aims to investigate how university image (program, facilities, reputation, and cost) and external environment (influences of peers and family and students’ achievement) have a relationship with students’ retention. A total of 300 university students participated in this study, which they were required to complete the online questionnaire.  This study employed a correlational study using a cross-sectional design and close-ended questions. Remarkably, the finding of the current study confirmed only one dimension of the university image, namely reputation, had a positive relationship with students’ retention. In contrast, university image attributes such as program, facilities, cost; and external environment, which is peer/family influence and achievement, have no relationship with students’ retention. Future recommendations are also discussed in dealing with the students' retention issues concerning students’ characteristics such as socioeconomic status and the mediating variable effects.